2016
DOI: 10.3892/mmr.2016.5962
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of epoxyeicosatrienoic acids in the liver and kidney of cytochrome P450 4F2 transgenic mice

Abstract: Abstract. Arachidonic acid (AA) can be metabolized into 20-hydroxyeicosatetraenoic acid (20-HETE) by ω-hydroxylases, and epoxyeicosatrienoic acids (EETs) by epoxygenases. The effects of EETs in cardiovascular physiology are vasodilatory, anti-inflammatory and anti-apoptotic, which are opposite to the function to 20-HETE. However, EETs are not stable in vivo, and are rapidly degraded to the biologically less active metabolites, dihydroxyeicosatrienoic acids, via soluble epoxide hydrolase (sEH). Western blotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition to prominent roles for eicosanoids in inflammation, they also play important roles in vasal tone and platelet activation. For example, HETEs exhibit prohypertensive effects through vasoconstriction and an antihypertensive effects through natriuresis 48,49 . Platelet activation and apoptotic pathways are increased in PWH, despite virologic suppression 50 , and thrombocytopenia is a common finding in PWH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to prominent roles for eicosanoids in inflammation, they also play important roles in vasal tone and platelet activation. For example, HETEs exhibit prohypertensive effects through vasoconstriction and an antihypertensive effects through natriuresis 48,49 . Platelet activation and apoptotic pathways are increased in PWH, despite virologic suppression 50 , and thrombocytopenia is a common finding in PWH.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HETEs exhibit prohypertensive effects through vasoconstriction and antihypertensive effects through natriuresis. 47 , 48 Platelet activation and apoptotic pathways are increased in PWH, despite virologic suppression, 49 and thrombocytopenia is a common finding in PWH. In addition to roles in vascular and tissue repair, they play central roles in innate immune activation by directly interacting with leukocytes and secreting cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, LPS decreases EET while increases 20-HETE ( Anwar-mohamed et al, 2010 ; Theken et al, 2011 ). The importance of the 20-HETE/EET ratio is supported by studies using CYP4F2 transgenic mice ( Zhang et al, 2016 ). In HCC, reduced expression of CYP2A6 modulates the anti-tumor immunity by disrupting the equilibrium between 20-HETE and EETs ( Jiang et al, 2021 ).…”
Section: Biological Functions Of Oxylipins In Liver Disease and Cance...mentioning
confidence: 99%
“…Recently, it was shown that the dysregulated renal 20‑HETE/EET ratio in the hypertensive Cyp4F2 transgenic mice was resulted from the activation of soluble epoxide hydrolase (sEH) and the inhibition of epoxygenase activity suggesting 20-HETE vasoconstrictive activity. Moreover, 20‑HETE demonstrated an inverse regulatory effect on the endogenous epoxygenases in the kidney [ 89 ].…”
Section: Role Of 20-hete In the Kidneymentioning
confidence: 99%
“…Recently, 20‑HETE demonstrated a counter regulatory effect on the endogenous epoxygenases in the liver. Thus the tuning of 20-HETE and EETs formation and degradation may provide therapeutic benefits; given that they have opposite effects in several diseases [ 89 , 140 ]. Interestingly, 20-HETE level in the urine of cirrhotic patients with ascites is much higher than in case of cirrhosis without ascites which in turn is higher than excretion rates in normal individuals [ 139 ].…”
Section: Role Of 20-hete In the Livermentioning
confidence: 99%